2021
DOI: 10.1126/science.abe9124
|View full text |Cite
|
Sign up to set email alerts
|

Canonical T cell receptor docking on peptide–MHC is essential for T cell signaling

Abstract: T cell receptor (TCR) recognition of peptide–major histocompatibility complexes (pMHCs) is characterized by a highly conserved docking polarity. Whether this polarity is driven by recognition or signaling constraints remains unclear. Using “reversed-docking” TCRβ-variable (TRBV) 17+ TCRs from the naïve mouse CD8+ T cell repertoire that recognizes the H-2Db–NP366 epitope, we demonstrate that their inability to support T cell activation and in vivo recruitment is a direct consequence of reversed docking polarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 61 publications
4
74
0
Order By: Relevance
“…In addition, we fitted our model to two datasets published by other labs: 1) soluble mouse N15 TCRαβ interacted with VSV and two MT peptides bound to H2-K b (Supplementary Fig. 1e) 6 and 2) four mouse TCRs expressed on hybridomas interacted with NP 366 bound to the D227K mutant of H-2D b to prevent CD8 binding 15 (Supplementary Fig. 1f).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we fitted our model to two datasets published by other labs: 1) soluble mouse N15 TCRαβ interacted with VSV and two MT peptides bound to H2-K b (Supplementary Fig. 1e) 6 and 2) four mouse TCRs expressed on hybridomas interacted with NP 366 bound to the D227K mutant of H-2D b to prevent CD8 binding 15 (Supplementary Fig. 1f).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed surprising features of reversed-polarity TRBV TCRs such that interactions of NP 366 :H-2D bD227K to TCRs B13.C1 and B17.C1 induced T cell signaling, whereas interactions of the same pMHC to B17.R1 and B17.R2 TCRs did not 15 . Despite that the former two TCRs formed catch-slip bonds with NP 366 :H-2D bD227K and the latter two TCRs formed slip-only bonds, the authors suggested that the signaling capability of the B13.C1 and B17.C1 TCRs could not be attributed to their force-prolonged bond lifetimes because the B17.C1 TCR-H-2D bD227K bond was shorter-lived than the B17.R2 TCR-NP 366 :H-2D bD227K bond across the entire force range tested.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, immune evasion frequently happens [19, 20]. In the classic two-signal model of T-cell activation, the primary signal (signal one) is triggered by the ligation of the peptide-MHC to the TCR-CD3 complex, where the TCR represents the only receptor involved [21, 22]. Signal two is generated by the transduction of co-activators or co-inhibitors in the immune synapse following a calcium influx [23, 24].…”
Section: Introductionmentioning
confidence: 99%